Increasing Production of Freedia Herbal SME Hippocrates Medika Palembang with the Application of Extraction Machine Technology - Hidayat, Rachmat; Hayati, Lusia; Parisa, Nita; Inggarsih, Rara (HM Publisher, 2022)
Indonesia is the second largest biodiversity-rich country in the world. Abundant biodiversity makes Indonesia rich in the potential of plants to be used as a variety of flavorful vegetables, dried fruit, medicine, and medicinal plants packaged in the form of herbs. Freedia is the flagship product of this SME, which is downstream from the innovative products of Rachmat Hidayat and the team. Freedia is an herb that is processed as a brewed drink to overcome diabetes mellitus disorder. The implementation of this activity uses methods of observation, interview, design, manufacturing, trial, application, and monitoring. Based on the results of the application of extraction machines in SME Hippocrates Medika, it can be concluded that the existence of these machines greatly supports the production process of freedia herbs three times more than before.